Hubungan Konsumsi Kopi Dengan Kejadian Dismenore : Sebuah Tinjauan Literatur - Aisyah Ramadhini; Elly Usman; Aladin Aladin (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Coffee is a widely consumed beverage especially for Indonesian. Its consumption continues to increase. There is not much information and researches on the relationship between coffee consumption and dysmenorrhea. This literature study was conducted to find out more about the relationship between coffee consumption and the incidence of dysmenorrhea. This literature study is a narrative literature review, delves into the literature with an analytical observational design regarding the relationship between coffee consumption and the incidence of dysmenorrhea. The literature search was carried out through the PubMed, Proquest and ScienceDirect electronic databases based on predetermined inclusion and exclusion criteria. A total of 12 literatures were reviewed. From the results of the literature review, there are six literatures which state that coffee consumption is associated with dysmenorrhea and six other literatures state that coffee consumption is not associated with dysmenorrhea. The conclusion of this literature study is that the relationship between coffee consumption and the incidence of dysmenorrhea is still debatable .